2014
DOI: 10.1126/science.1250808
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Complex on the Verge of Breakdown: Isolation of the Elusive Cyanoformate Ion

Abstract: Why does cyanide not react destructively with the proximal iron center at the active site of 1-aminocyclopropane-1-carboxylic acid (ACC) oxidase, an enzyme central to the biosynthesis of ethylene in plants? It has long been postulated that the cyanoformate anion, [NCCO2]–, forms and then decomposes to carbon dioxide and cyanide during this process. We have now isolated and crystallographically characterized this elusive anion as its tetraphenylphosphonium salt. Theoretical calculations show that cyanoformate h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 60 publications
4
58
1
Order By: Relevance
“…We found that the total levels of cyanide/ thiocyanate measured using the isonicotinic-barbituric acid method were comparable with and without formaldehyde treatment, indicating that the chemical we detected using the isonicotinic-barbituric acid method in the liquid media samples is thiocyanate ion, not cyanide. This is consistent with the previous finding that cyanide from the biosynthesis of ethylene can be rapidly removed (Miller and Conn, 1980;Yip and Yang, 1988;Murphy et al, 2014). It was reported that cyanide plays a role in rice resistance against blast fungus (Seo et al, 2011).…”
Section: Accumulation Of Thiocyanate In Response To Pathogensupporting
confidence: 93%
“…We found that the total levels of cyanide/ thiocyanate measured using the isonicotinic-barbituric acid method were comparable with and without formaldehyde treatment, indicating that the chemical we detected using the isonicotinic-barbituric acid method in the liquid media samples is thiocyanate ion, not cyanide. This is consistent with the previous finding that cyanide from the biosynthesis of ethylene can be rapidly removed (Miller and Conn, 1980;Yip and Yang, 1988;Murphy et al, 2014). It was reported that cyanide plays a role in rice resistance against blast fungus (Seo et al, 2011).…”
Section: Accumulation Of Thiocyanate In Response To Pathogensupporting
confidence: 93%
“…The key aspect in isolating ACO was the addition of ascorbic acid (vitamin C) to the extraction media, as was first reported by Ververidis and John (1991) who isolated ACO from melon tissue and quantified in vitro ACO activity. Although the exact role of ascorbic acid for protein stability/activity remained uncertain for a long time (Rocklin et al, 2004), it was recently clarified that ascorbic acid participates in the ring opening of ACC, by providing a single-electron to the active site (Murphy et al, 2014). This catalytic reaction releases ethylene and a cyanoformate ion [NCCO 2 ] - , which is subsequently decomposed into CO 2 and CN - (Murphy et al, 2014).…”
Section: Acc and Ethylene Biosynthesismentioning
confidence: 99%
“…45 Both of these complexes were prepared through direct exposure of the fluoride or cyanide precursor salts to CO2. 154 cyanoformate (middle) 162 and nitryl cyanide (right) 163 ions. Crystallographically determined bond lengths (Å) for fluorocarbonate and cyanoformate are included.…”
Section: C Halide and Pseudo-halide Adducts Of Co2mentioning
confidence: 99%
“…154 Murphy et al observed the same tendency toward hydrolysis, isolating crystals of tetraphenylphosphonium bicarbonate hydrate. 162 The cyanoformate ion has been shown, by both experiment and computation, to be on the verge of dissociation. In situ infrared analysis revealed that cyanoformate fragments into its constituents in polar media (e.g., acetonitrile), while in non-polar media (e.g., toluene) it was stable for a longer time.…”
Section: C Halide and Pseudo-halide Adducts Of Co2mentioning
confidence: 99%